# 12x+2(x+8)+6=8-(-4x+6)

## Simple and best practice solution for 12x+2(x+8)+6=8-(-4x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 12x+2(x+8)+6=8-(-4x+6) equation:

12x+2(x+8)+6=8-(-4x+6)
We move all terms to the left:
12x+2(x+8)+6-(8-(-4x+6))=0
We multiply parentheses
12x+2x-(8-(-4x+6))+16+6=0

We calculate terms in parentheses: -(8-(-4x+6)), so:
8-(-4x+6)
determiningTheFunctionDomain
-(-4x+6)+8
We get rid of parentheses
4x-6+8
We add all the numbers together, and all the variables
4x+2
Back to the equation:
-(4x+2)

We add all the numbers together, and all the variables
14x-(4x+2)+22=0
We get rid of parentheses
14x-4x-2+22=0
We add all the numbers together, and all the variables
10x+20=0
We move all terms containing x to the left, all other terms to the right
10x=-20
x=-20/10
x=-2

`